A method for calculating the anion and cation sites of sulfur-doped lithium titanate

CN113192577BActive Publication Date: 2025-02-25SOUTHEAST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202110463678.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-04-26
Publication Date
2025-02-25
Estimated Expiration
2041-04-26

AI Technical Summary

Technical Problem

The negative electrode material of lithium-ion battery graphite has a safety hazard due to the unsatisfactory growth and cycle stability of dendritic lithium. Moreover, the lithium ion diffusion coefficient and conductivity of lithium titanate are low, which affects its electrochemical performance.

Method used

By establishing a ternary equilibrium phase diagram of Li-Ti-O, using first-principle calculations, we predict the defect formation energy and electrical properties of sulfur-doped lithium titanate, and determine the priority of sulfur-doped sites and preparation environment.

Benefits of technology

It improves the electrochemical performance of lithium titanate materials, regulates its conductivity and lithium ion diffusion coefficient, and enhances the cyclic stability and safety of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113192577B_ABST
    Figure CN113192577B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for calculating the anion and cation sites of sulfur-doped lithium titanate, establishing a ternary equilibrium phase diagram of Li-Ti-O; establishing a model of lithium titanate perfect supercell, defect system and constituent phases of the ternary phase diagram, and performing structural optimization; using first principles to calculate the defect formation energy of sulfur doping at different sites; and calculating the electrical properties of the perfect unit cell and defect unit cell respectively. The method of the present invention has certain significance for improving the electrochemical performance and defect control of lithium titanate materials as negative electrode materials for lithium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material simulation, and in particular to a method for calculating anion and cation sites of sulfur-doped lithium titanate. Background Art

[0002] As an indispensable part of energy storage devices, lithium-ion batteries (LIBs) have achieved great success in automobiles and mobile devices. However, the main anode material, graphite, faces safety risks due to the growth of dendritic lithium and unsatisfactory cycle stability, especially at high charge and discharge rates.

[0003] Spinel lithium titanate (Li4Ti s Q 12 ) is considered to be a promising alternative to graphite anode, although its theoretical capacity is 175mA hg -1 Smaller than graphite, but its excellent cycle stability and safety have attracted widespread attention. Its high electrochemical platform (1.55V vs. Li / Li + ), avoiding the formation of dendritic lithium crystals and solid electrolyte interphase (SEI) layer. 12 Known as the "zero strain" material, it forms the lithiated phase Li7Ti5Q 12 The volume change of Li4Ti5Q is less than 1%, which ensures good structural stability for long-term cycling. 12 The lithium ion diffusion coefficient (10 -9 -10 -16 cm 2 s -1 ) and conductivity (10 -8 -10 -13 S cm -1 ) is low, thus seriously compromising its electrochemical performance.

[0004] In order to improve Li4Ti5Q 12 The researchers doped heterogeneous atoms into the lattice to effectively improve the inherent electronic and ionic conductivity. Since lithium titanate contains two possible doping sites, Ti and O, it is cumbersome and costly to verify the doping sites through experiments. At the same time, there are certain difficulties in observing its microscopic electronic structure and explaining its mechanism. Therefore, theoretical calculation has become an important means to understand lithium titanate materials.

[0005] Sulfur (S) is a homologous element of oxygen and is widely used to dope oxides. However, there is little research on the effect of S doping on Li4Ti5O 12 Meanwhile, sulfur has different valences, including S 2- , S 4+ and S6+ , S can be doped at anion or cation sites. Therefore, predicting sulfur-doped lithium titanate sites is of great significance for the exploration of lithium titanate materials as negative electrode materials for lithium-ion batteries. Summary of the invention

[0006] Purpose of the invention: The purpose of the present invention is to provide a method for calculating the anion and cation sites of sulfur-doped lithium titanate, by establishing a Li-Ti-O ternary equilibrium phase diagram, and calculating μ Li , μ Ti and μ O The chemical potential plays a limiting role, and the defect formation energy at different phase equilibrium points is calculated using first principles. The relationship between the defect formation energy of sulfur-doped lithium titanate and the chemical potential during the preparation process is obtained, and the changes in electrical properties after doping can be calculated.

[0007] Technical solution: A method for calculating the anion and cation sites of sulfur-doped lithium titanate according to the present invention comprises the following steps:

[0008] (1) Establish the ternary equilibrium phase diagram of Li-Ti-O.

[0009] (2) Establish a model of the perfect supercell, defect system and related component phases of lithium titanate ternary phase diagram and perform structural optimization.

[0010] (3) The defect formation energy of sulfur doping at different sites was calculated using first principles.

[0011] (4) Calculate the electrical properties of the perfect unit cell and the defective unit cell respectively.

[0012] In step (1), according to Li4Ti5Q 12 The stability conditions and possible related phases of Li-Ti-O were used to establish a ternary equilibrium phase diagram, and the chemical potential (μ i ) is limited. 12 In compounds, the defect formation energy depends on the atomic chemical potential (μ i ), μ i The values ​​are subject to different thermodynamic constraints. 12 Compounds, stability must meet the following conditions:

[0013]

[0014] Chemical potential μ i The lower limit of is determined by the above conditions. In addition, the conditions that avoid the formation of large amounts of Li, Ti and O2 gases make the chemical potential μ i There is an upper limit of μ ≤ 0. At the same time, further restrictions imposed by other related Li-Ti-O phases are still needed to control μi Stronger restrictions are imposed. Considering the available chemical potentials of the constituent elements, constraints should be imposed on all possible relevant constituent phases. Possible relevant constituent phases are: Q2, Ti, Li, Ti2Q3, TiQ2, Li2Q, Li2O2.

[0015] In step (1), for different given points in the ternary phase diagram, the host material is in equilibrium with different related phases and corresponds to a specific set of variables μ Li , μ Ti and μ O .

[0016] In step (2), it is necessary to construct a crystal model of a perfect supercell of lithium titanate and a defect system, wherein an n-type unit cell (Li l0 Ti 10 Q 32 , 2Li atoms at the 16d position) and two p-type unit cells (Li 11 Ti 15 O 32 , 3Li atoms at the 16d position) to construct Li 32 Ti 40 O 96 The supercell is constructed to meet the stoichiometric ratio. There are two doping sites for the establishment of lithium titanate defect supercells: Li doped at the Ti site 32 Ti 39 SO 96 , Li doped at O ​​site 32 Ti 40 O 95 S.

[0017] In step (2), possible related phases in the phase diagram are O2, Ti, Li, Ti2O3, TiO2, Li2O, and Li2O2.

[0018] In step (2), the first principle calculation is performed on the established model, the structure is optimized and the total energy of the system is obtained.

[0019] In step (3), the first principles calculation refers to an algorithm that directly solves the Schrödinger equation based on the principles of interaction between atomic nuclei and electrons and their basic laws of motion, using the principles of quantum mechanics, and after some approximate processing based on specific requirements. This is customarily called the first principles.

[0020] In step (3), the formula for calculating the defect formation energy of lithium titanate at different doping sites is as follows:

[0021] E f (D)=E tot (D-doped)-[E tot(pure)+μ D -μ E ]

[0022] Among them, E f (D) is the defect formation energy of the system when doping D element at the E site;

[0023] E tot (D-doped) is the total energy of the supercell when doped with D element;

[0024] E tot (pure) is the total energy of a perfect supercell without defects;

[0025] μ D is the chemical potential of doping element D;

[0026] μ E is the chemical potential of doping D element to replace the E site.

[0027] In step (4), for the perfect cell Li 32 Ti 40 O 96 , containing doped defective cell Li 32 Ti 39 SO 96 , Li 32 Ti 40 O 95 The S-type state density is calculated to obtain the electronic properties of the lithium titanate system after doping, and to predict the changes in the electrochemical performance when lithium titanate is used as the negative electrode material of lithium-ion batteries.

[0028] Among them, the first principle calculations, such as the calculation of the total energy of the unit cell and the calculation of the defect formation energy, are implemented based on the Vienna ab initio simulation package (VASP) simulation software package based on density functional theory calculations. In the calculation process, the projected augmented plane wave pseudopotential (PAW) method is used, and the PBE exchange correlation function is described based on the generalized gradient approximation (GGA). The plane wave cutoff energy is 600eV and the mechanical convergence standard is The self-consistent convergence criterion is 10 - 5 eV.

[0029] Technical difficulties: The present invention is based on Li4Ti5O 12 Starting from TiO2 with the same lithium insertion mechanism, the chemical potential change of the binary system is extended to the ternary system. The binary system TiO2 only needs to consider the simple equilibrium state of Ti, O2, and TiO2 in the two cases of oxygen-rich and titanium-rich. This method takes into account the equilibrium state of Li4Ti5O by establishing the Li-Ti-O ternary equilibrium phase diagram. 12The influence of possible related phases on the chemical potential of O, Ti, and Li, as well as the equilibrium state of mutual influence between different related phases. By analyzing the priority of sulfur atom doping sites in oxygen-rich, titanium-rich, and lithium-rich phases, the experimental design can be better guided.

[0030] Through the calculation method of the present invention, it is predicted that when thiourea (oxygen-rich conditions) is selected as the sulfur source, S atoms are more likely to be substituted on the Ti site, and when TiS2 (Ti-rich conditions) is selected as the sulfur source, S atoms are more likely to be substituted on the O site. The method of the present invention has a certain significance for improving the electrochemical performance and defect control of lithium titanate materials as negative electrode materials for lithium ion batteries.

[0031] Beneficial effects:

[0032] (1) The present invention provides a method for predicting sulfur-doped lithium titanate sites based on a ternary phase diagram, describes the relationship and formation rules between the internal defect formation energy of the material and the external preparation environment, and can achieve the purpose of regulating the material by selecting different preparation raw materials.

[0033] (2) The present invention adopts the first principle calculation based on density functional theory, and the Li4Ti5Q can be obtained by inputting basic information such as atomic position and element pseudopotential. 12 The defect formation energy and electronic properties make up for the lack of understanding of the basic physics of materials during material application, and can provide better theoretical research and reference value for existing materials.

[0034] (3) Since the present invention adopts a computational approach and utilizes the rapidly developing modern Internet technology, it effectively reduces the high cost of experimental equipment and experimental materials, and the entire process is visual, clear, and controllable. In summary, this method predicts the priority of doping sites of lithium titanate under different preparation environments through first-principles calculations. At the same time, the electrochemical performance is predicted through subsequent state density analysis, and relevant experiments are designed for verification, which proves the effectiveness of this method. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a principle flow chart of the present invention;

[0036] Figure 2 Schematic diagram of a perfect supercell structure of lithium titanate provided by an example of the present invention;

[0037] Figure 3 It is the Li-Ti-O ternary equilibrium phase diagram established by the present invention;

[0038] Figure 4 Schematic diagram of defect formation energy of lithium titanate under different preparation conditions calculated by the present invention;

[0039] Figure 5It is the perfect lithium titanate unit cell Li calculated by the present invention. 32 Ti 40 O 96 Schematic diagram of the density of states;

[0040] Figure 6 is the defective lithium titanate cell Li calculated by the present invention 32 Ti 39 5O 96 Schematic diagram of the density of states;

[0041] Figure 7 is the defective lithium titanate cell Li calculated by the present invention 32 Ti 40 SO 95 Schematic diagram of the density of states. DETAILED DESCRIPTION

[0042] The present invention is further described in detail below with reference to the embodiments.

[0043] A method for calculating the anion and cation sites of sulfur-doped lithium titanate comprises the following steps:

[0044] (1) Establish the ternary equilibrium phase diagram of Li-Ti-O.

[0045] According to Li4Ti5O 12 The stability conditions and possible related phases of Li-Ti-O were used to establish a ternary equilibrium phase diagram, and μ i Limitation. 12 In compounds, the defect formation energy depends on the atomic chemical potential (μ i ), μ i The values ​​are subject to different thermodynamic constraints. For the ternary Li4Ti5O 12 Compounds, stability must meet the following conditions:

[0046]

[0047] Chemical potential μ i The lower limit of is determined by the above conditions. In addition, the conditions that avoid the formation of large amounts of Li, Ti and O2 gases make the chemical potential μ i There is an upper limit of μ ≤ 0. At the same time, further restrictions imposed by other related Li-Ti-O phases are still needed to control μ i Stronger restrictions are imposed. Considering the available chemical potentials of the constituent elements, constraints should be imposed on all possible relevant constituent phases. Possible relevant constituent phases are: O2, Ti, Li, Ti2O3, TiO2, Li2O, Li2O2.

[0048] For a given point in the ternary phase diagram, the host material is in equilibrium with the different associated phases and corresponds to a specific set of variables μ Li , μ Ti and μ O As in condition A, Li2O, Li2O2 and Li4Ti5O 12 In a state of balance.

[0049] The equilibrium phase diagram should satisfy the following relationship at the seven phase points of AG:

[0050] Point A:

[0051]

[0052]

[0053]

[0054] Point B:

[0055]

[0056]

[0057]

[0058] Point C:

[0059]

[0060]

[0061]

[0062] Point D:

[0063]

[0064]

[0065]

[0066] Point E:

[0067]

[0068] μ Ti =μ Ti(bulk)

[0069]

[0070] Point F:

[0071]

[0072] μ Ti =μ Ti(bulk)

[0073] μ Li =μ Li(bulk))

[0074] G-spot:

[0075]

[0076]

[0077] μ Li =μ Li(bulk)

[0078] By changing the seven phase equilibrium points in different preparation environments, the chemical potentials of O, Ti, and Li are obtained respectively.

[0079] Chemical potential μ of element S S It can be simply obtained by DFT and To deduce:

[0080]

[0081] (2) Establish a model of the perfect supercell, defect system and related component phases of lithium titanate ternary phase diagram and perform structural optimization.

[0082] Construct a perfect lithium titanate crystal structure model: the lattice parameters are Spinel Li4Ti5O 12 (Fd-3m space group 227) contains eight [Li] 8a [Li 1 / 3 Ti 5 / 3 ] 16d [O4] 32e In this model, an n-type unit cell (Li 10 Ti 10 O 32 , 2Li atoms at the 16d position) and two p-type unit cells (Li 11 Ti 15 O 32 , 3Li atoms at the 16d position) form a supercell (Li 32 Ti 40 O 96 ) to satisfy the stoichiometric ratio.

[0083] The perfect lithium titanate crystal is arranged in the most stable manner, and the Li coordinates at the 16d position are (0.375, 0.875, 0.125), (0.625, 0.625, 0.625), (0.125, 0.375, 0.875), (0.875, 0.125, 0.458), (0.375, 0.375, 0.542), (0.625, 0.125, 0.708), (0.125, 0.875, 0.792), (0.875, 0.625, 0.958).

[0084] Two defect system crystal models were constructed: Li doped on the Ti site 32 Ti 39 SO 96 , Li doped on O site 32 Ti 40 O 95 S.

[0085] The possible related phases in the ternary phase diagram are O2, Ti, Li, Ti2O3, TiO2, Li2O, Li2O2.

[0086] The unit cell of the above compounds was constructed using Materials Studio software.

[0087] Export the constructed three-dimensional crystal structure cif file to POSCAR.vasp format.

[0088] The .vasp file uses an inverted lattice vector.

[0089] Perform first-principles calculations on the established model, optimize the structure and obtain the total energy of the system.

[0090] The first-principles calculations described above were all performed using the Vienna ab initiosimulation package (VASP) simulation software package based on density functional theory calculations. In the calculation process, the projected augmented plane wave pseudopotential (PAW) method was used, and the PBE exchange-correlation function was described based on the generalized gradient approximation (GGA). The plane wave cutoff energy was 600 eV and the mechanical convergence standard was The self-consistent convergence criterion is 10 -5 eV.

[0091] Li 32 Ti 40 O 96 The lattice parameters of the optimized crystal structure are The error is less than 0.8%.

[0092] (3) The defect formation energy of sulfur doping at different sites was calculated using first principles.

[0093] By different chemical potential μ at different phase equilibrium points i , calculated the variation of defect formation energy of sulfur at O ​​site and Ti site of lithium titanate

[0094] The calculation formula of defect formation energy at different doping sites is:

[0095] E f (D)=E tot (D-doped)-[E tot (pure)+μ D -μ E ]

[0096] Among them, E f (D) is the defect formation energy of the system when doping D element at the E site;

[0097] E tot (D-doped) is the total energy of the supercell when doped with D element, here Li 32 Ti 39 SO 96 , Li 32 Ti 40 O 95 The total energy of S;

[0098] E tot (pure) is the total energy of a perfect supercell without defects, here Li 32 Ti 40 O 96 ;

[0099] μ D is the chemical potential of doping element D;

[0100] μ E is the chemical potential of doping element D to replace element E site (here O or Ti)

[0101] By calculation, S tends to replace the 16d Ti site at A, B, and C sites under Li / Ti-rich conditions and replace the 32e O site under O-rich conditions under D, E, F, and G. Therefore, the choice of sulfur source plays a crucial role in the position where S is replaced.

[0102] (4) Calculate the electrical properties of the perfect unit cell and the defective unit cell respectively.

[0103] For a perfect cell Li 32 Ti 40 O 96 , containing doped defective cell Li 32 Ti39 SO 96 , Li 32 Ti 40 O 95 The S-type state density is calculated to obtain the electronic properties of the lithium titanate system after doping, and to predict the changes in the electrochemical performance when lithium titanate is used as the negative electrode material of lithium-ion batteries.

[0104] from Figure 5 It can be seen that the original Li 32 Ti 40 O 96 The band gap value is 2.37eV. Figure 6 It can be seen that S doped Li on the Ti site 32 Ti 39 5O 96 The band gap is 1.45 eV, from Figure 7 It can be seen that Li doped on the O site 32 Ti 40 O 95 The S band gap is 1.42eV. After sulfur atom doping, the band gap decreases. In addition, a new peak appears near the Fermi level, and the conduction band moves to the left, improving the conductivity.

[0105] Therefore, this method predicts that when thiourea (oxygen-rich conditions) is used as the sulfur source, S atoms are more likely to replace on the Ti site, and when TiS2 (Ti-rich conditions) is used as the sulfur source, S atoms are more likely to replace on the O site.

[0106] The present invention provides a method for calculating the anion and cation sites of sulfur-doped lithium titanate, predicts the priority level of sulfur atom doping sites under different preparation environments, explains the relationship and formation law between the internal defect formation energy of the material and the external preparation environment, and can achieve the purpose of regulating the material by selecting different preparation raw materials.

Claims

1. A method for calculating the anion and cation sites of sulfur-doped lithium titanate, characterized in that: The following steps are involved: (1) Establish the ternary equilibrium phase diagram of Li-Ti-O; (2) Establish models of lithium titanate perfect supercell, defect system and ternary phase diagram components, and perform structural optimization (3) Calculate the defect formation energy of sulfur doping at different sites using first principles; (4) Calculate the electrical properties of the perfect unit cell and the defective unit cell respectively.

2. The method for calculating the anion and cation sites of sulfur-doped lithium titanate according to claim 1, characterized in that: In step (1), according to the ternary Li4Ti s O 12 The stability conditions and composition phases of the compound establish a ternary equilibrium phase diagram, and the stability conditions meet The constituent phases are O2, Ti, Li, Ti2O3, TiO2, Li2O and Li2O2; Among them, μ i represents the atomic chemical potential of the constituent elements, i is Li4Ti5O 12 、Li、Ti、O。 3. The method for calculating the anion and cation sites of sulfur-doped lithium titanate according to claim 1, characterized in that: Step (2) includes: constructing lithium titanate Li 32 Ti 40 O 96 Perfect supercell to meet the stoichiometric ratio; the establishment of lithium titanate defect supercell is divided into Li doped at the Ti site 32 Ti 39 SO 96 As well as Li doped at O ​​sites 32 Ti 40 O 95 S; and perform first-principles calculations on the established model, optimize the structure and obtain the total energy of the system.

4. The method for calculating the anion and cation sites of sulfur-doped lithium titanate according to claim 1, characterized in that: In step (3), by calculating the defect formation energy, different energy change laws at the O site and the Ti site are obtained, thereby predicting the site where the element is most easily doped; The formula for calculating the defect formation energy of lithium titanate at different doping sites is as follows: AND f (D)=E tot =(D-doped)-[E tot (pure)+µ D -μ E ]: Among them, E f (D) is the defect formation energy of the system when doping D element at the E site; E tot (D-doped) is the total energy of the supercell when doped with D element; E tot (pure) is the total energy of a perfect supercell without defects; μ D is the chemical potential of doping element D; μ E is the chemical potential of doping element D to replace element E site.

5. The method for calculating the anion and cation sites of sulfur-doped lithium titanate according to claim 1, characterized in that: In step (4), for the perfect unit cell Li 32 Ti 40 O 96 , containing doped defective cell Li 32 Ti 39 SO 96 , Li 32 Ti 40 O 95 The S-type state density is calculated to obtain the electronic properties of the lithium titanate system after doping, and to predict the changes in the electrochemical performance when lithium titanate is used as the negative electrode material of lithium-ion batteries.

6. The method for calculating the anion and cation sites of sulfur-doped lithium titanate according to claim 1, characterized in that: The first-principles calculations were performed using the VASP software based on density functional theory, using the projected plane wave pseudopotential method, and using the PBE exchange-correlation function based on the generalized gradient approximation. The plane wave cutoff energy was 600 eV and the mechanical convergence standard was The self-consistent convergence criterion is 10 -5 eV.